Examining Business Undergraduate Students’ Intention for Creating Sustainable Entrepreneurship in Indonesia - Pribadi, Henry (Universitas Prasetiya Mulya, 2023)
This paper examined how intention to create sustainability entrepreneurship among undergraduate business students is influenced by various variables. Implementing the theory of planned behaviors from previous research, a framework model is created and analyzes a sample of undergraduate students majoring in business at Universitas Prasetiya Mulya, Indonesia. The result of this research provides an initial picture of how various antecedents affect the intention of sustainability entrepreneurship compared to previous research in Indonesia. Practical findings suggested that, in order to leverage the intention to participate in sustainability entrepreneurship, it is imperative to focus more on creating intrinsic motivation for next-generation entrepreneurs by implementing an integrative approach in the educational context with a focus on real-life, action-based sustainability projects and focus more in utilizing digital platform and social media.